2020
DOI: 10.3390/molecules25133029
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interaction of Organophosphono- and Organophosphorothioates with Human Acetylcholinesterase

Abstract: The implementation of the Chemical Weapons Convention (CWC) in 1997 was a milestone in the prohibition of chemical warfare agents (CWA). Yet, the repeated use of CWA underlines the ongoing threat to the population. Organophosphorus (OP) nerve agents still represent the most toxic CWA subgroup. Defensive research on nerve agents is mainly focused on the “classical five”, namely tabun, sarin, soman, cyclosarin and VX, although Schedule 1 of the CWC covers an unforeseeable number of homologues. Likewise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As it was mentioned earlier, OPCs are designed to inhibit serine hydrolases, including cholin- and carboxylesterases [ 77 ]. Nevertheless, it is possible to tune on their activity with OPCs while genetically modifying these enzymes.…”
Section: Inversion Of Inhibition To Biocatalysis: Cholin- and Carmentioning
confidence: 99%
“…As it was mentioned earlier, OPCs are designed to inhibit serine hydrolases, including cholin- and carboxylesterases [ 77 ]. Nevertheless, it is possible to tune on their activity with OPCs while genetically modifying these enzymes.…”
Section: Inversion Of Inhibition To Biocatalysis: Cholin- and Carmentioning
confidence: 99%
“…Our docking experiments showed that this inhibition is likely due to active-site interactions similar to that of donepezil, particularly with W286 in the PAS. The results of this study may also be important from both a drug discovery and toxicological perspective as we search for drugs to address pesticide and nerve agent poisoning …”
Section: Introductionmentioning
confidence: 97%
“…The results of this study may also be important from both a drug discovery and toxicological perspective as we search for drugs to address pesticide and nerve agent poisoning. 41 ■ EXPERIMENTAL SECTION Chemicals and Reagents. Tilorone dihydrochloride (Item No.…”
Section: ■ Introductionmentioning
confidence: 99%